Aligning organisational priorities and implementation science for cancer research - Stephanie Best; Karin Thursky; Mark Buzza; Marlena Klaic; Sanne Peters; Lisa Guccione; Alison Trainer; Jillian Francis (BMC, 2024)
Abstract Background The challenge of implementing evidence into routine clinical practice is well recognised and implementation science offers theories, models and frameworks to promote investigation into delivery of evidence-based care. Embedding implementation researchers into health systems is a novel approach to ensuring research is situated in day-to-day practice dilemmas. To optimise the value of embedded implementation researchers and resources, the aim of this study was to investigate stakeholders' views on opportunities for implementation science research in a cancer setting that holds potential to impact on care. The research objectives were to: 1) Establish stakeholder and theory informed organisation-level implementation science priorities and 2) Identify and prioritise a test case pilot implementation research project. Methods We undertook a qualitative study using semi-structured interviews. Participants held either a formal leadership role, were research active or a consumer advocate and affiliated with either a specialist cancer hospital or a cancer alliance of ten hospitals. Interview data were summarised and shared with participants prior to undertaking both thematic analysis, to identify priority areas for implementation research, and content analysis, to identify potential pilot implementation research projects. The selected pilot Implementation research project was prioritised using a synthesis of an organisational and implementation prioritisation framework - the organisational priority setting framework and APEASE framework. Results Thirty-one people participated between August 2022 and February 2023. Four themes were identified: 1) Integration of services to address organisational priorities e.g., tackling fragmented services; 2) Application of digital health interventions e.g., identifying the potential benefits of digital health interventions; 3) Identification of potential for implementation research, including deimplementation i.e., discontinuing ineffective or low value care and; 4) Focusing on direct patient engagement e.g., wider consumer awareness of the challenges in delivering cancer care. Six potential pilot implementation research projects were identified and the EMBED project, to support clinicians to refer appropriate patients with cancer for genetic testing, was selected using the synthesised prioritisation framework. Conclusions Using a theory informed and structured approach the alignment between strategic organisational priorities and implementation research priorities can be identified. As a result, the implementation research focus can be placed on activities with the highest potential impact.